Reported User-Generated Online Hate Speech: The ‘Ecosystem’, Frames, and Ideologies - Iztok Šori; Vasja Vehovar (Social Sciences, 2022)
The spread of hate speech challenges the health of democracy and media systems in contemporary societies. This study aims to contribute to a better understanding of user-generated online hate speech reported by Internet users to national monitoring organizations, in particular its ‘ecosystem‘, discursive elements, and links to political discourses. First, we analyzed the main characteristics of the reported statements (source, removal rate, and targets) to reveal the media and political context of reported user-generated online hate speech. Next, we focused on hate speech statements against migrants and analyzed their discursive elements with the method of critical frame analysis (frames, actors, metaphors, and references) to understand the corresponding discourse. The main discursive feature of these statements is the prognosis, which calls for death and violence, so we could label this communication as ‘executive speech.’ Other key features are references to weapons and Nazi crimes from WWII, indicating the authors’ extreme-right ideological convictions, and the metaphors, employed to provoke disgust from migrants, present them as culturally inferior and raise fears about their supposed violent behavior. The corresponding diagnoses frame migrants as a threat in a similar way to populist political discourses of othering and complement these in providing ‘final’ solutions in prognoses.